Meningkatkan Aktivitas dan Hasil Belajar Matematika Menggunakan Kombinasi PBL, TPS dan CRH di Sekolah Dasar - Try Suci Septiana; Ahmad Muhyani Rizalie (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
In this study, problems can be found with low activity and student learning outcomes because students still do not understand learning and do not participate in learning. As for the solution to overcome these problems, researchers used a combination of PBL, TPS and CRH models. With the aim of this research to know the activities of students and teachers and improve student learning outcomes. This study uses a type of Classroom Action Research (CAR) with a qualitative approach, in this study conducted for 4 meetings. The research subjects were fifth grade students who were at Sungai Miai 8 Elementary School Banjarmasin with 18 students. The results of this study showed that there was an increase in teacher activity from meeting I reaching a score of 64 in the "Good" category and at meeting IV reaching a score of 97 with the "Very Good" category. Student activity at meeting I reached a score of 57 with the category "Quite Active" there was an increase in meeting IV reaching a score of 84 with the category "Very Active". Likewise, the learning outcomes in both the cognitive domain increased to 94%, while the affective and psychomotor domains increased to 100%.